Combining Teaching and Library Work: the Hybrid Academic - Sheridan, Dorothy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
This paper focuses on some of the issues raised when professional library staff combine archive management with an active teaching role, drawing on my own experience as an archivist in the University of Sussex Library. There are of course many archivists who are also teachers on professional training courses for prospective archivists but my concern here is teaching in higher education in subject areas other than library, archive and information sciences while using archival resources.